Strategi Pengembangan Komoditas Unggulan Perikanan Tangkap di Kabupaten Teluk Bintuni dalam Mendukung Perekonomian Daerah - Siti Nur Azisyah; Asep Hariyanto (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract. Fisheries production in Teluk Bintuni Regency is still far from the existing production potential, where in 2020 it was only 893.41 tons. This analysis uses mixed methods with the aim of knowing the leading commodities, the role of leading commodities and the right strategy in Teluk Bintuni Regency in the capture fisheries sector. The method used is secondary data collection through institutions and primary data through interviews and observations. To analyze the data, Location Quantient, Shift Share, Porter's Diamond Theory and SWOT analysis techniques were used. Based on the results of the analysis, it is known that the leading commodities in Teluk Bintuni Regency are crab, manyung, sembilang and shrimp which can be the main driving commodity in the capture fisheries sector. Based on the results of the LQ<1 and Shift Share<0 analysis and the comparison score of porter's diamond theory, it is concluded that the contribution of capture fisheries to the economy does not have a special role. SWOT analysis obtained diagram results are in quadrant 1. The strategy used has strengths and opportunities. For this reason, the strategy on S-O is (1) Preparation of regulations / policies in supporting integrated and sustainable resource management and utilization (2) Making innovations in producing other products from superior commodity catches, namely, crabs, Manyung, sembilang and shrimp. (3)Increase the production of commodity catches of Black Bawal, White Bawal, Gulamah, Black Snapper, White Snapper, Grouper, Kuwe, Layur, Manyung, Pari and Sembilang which are included in reef and demersal fish species. (4) Improvement of adequate facilities and infrastructure such as the average type of boat used by fishermen >10GT, using technology such as GPS and Image. The existing TPI is utilized according to its function, improving the infrastructure of the Bintuni-Sorong and Bintuni-Manokwari trans roads and (5)Improving the function of cooperatives for fishermen. Abstrak. Produksi perikanan di Kabupaten Teluk Bintuni masih jauh dari potensi produksi yang ada, dimana pada tahun 2020 hanya sebesar 893,41 ton. Analisis ini menggunakan mixed method dengan tujuan yaitu mengetahui komoditas unggulan, peranan komoditas unggulan serta strategi yang tepat di Kabupaten Teluk Bintuni pada sektor perikanan tangkap. Metode yang digunakan yaitu pengumpulan data sekunder melalui instansional dan data primer melalui wawancara dan observasi. Untuk menganalisis data digunakan teknik analisis Location Quantient, Shift Share, Teori Berlian Porter dan SWOT. Berdasarkan hasil analisis diketahui komoditas unggulan di Kabupaten Teluk Bintuni yaitu kepiting, manyung, sembilang dan udang yang dapat menjadi komoditas penggerak utama pada sektor perikanan tangkap. Berdasarkan hasil analisis LQ<1 dan Shift Share<0 dan skor perbandingan teori berlian porter disimpulkan kontribusi perikanan tangkap untuk perekonomian belum memiliki peran khusus. Analisis SWOT didapatkan hasil diagram berada pada kuadran 1. Strategi yang digunakan memiliki kekuatan dan peluang. Untuk itu strategi pada S-O yaitu (1)Penyusunan regulasi/kebijakan dalam mendukung pengelolaan dan pemanfaatan sumber daya secara terpadu serta berkelanjutan (2)Membuat inovasi dalam memproduksi produk lain dari hasil tangkapan komoditas unggulan yaitu, Kepiting, Manyung, sembilang dan udang. (3)Meningkatkan produksi hasil tangkap komoditas Bawal Hitam, Bawal Putih, Gulamah, Kakap Hitam, Kakap Putih, Kerapu, Kuwe, Layur, Manyung, Pari dan Sembilang yang termasuk pada jenis ikan karang dan demersal. (4)Peningkatan sarana dan prasarana yang memadai seperti rata-rata jenis kapal yang digunakan nelayan >10GT, menggunakan teknologi seperti GPS dan Citra. TPI yang ada dimanfaatkan sesuai fungsinya, melakukan perbaikan infrastruktur jalan trans Bintuni-Sorong dan Bintuni-Manokwari dan (5)Meningkatkan fungsi koperasi untuk nelayan.